A U-snRNA gene-specific upstream element and a -30 'TATA box' are required for transcription of the U2 snRNA gene of Arabidopsis thaliana. - Vankan, P (1989)
The U2 and U5 snRNA genes of Arabidopsis thaliana contain in their promoter regions two elements with conserved sequence and position. To test the significance of this conservation we have made a construction in which the promoter of the U2 RNA gene is replaced by the synthetic 98 bp long sequence containing the two conserved elements: an upstream sequence element, GTCCCACATCG (USE, pos. -78 to -68), and a TATA-like sequence TATAAATA (-33 to -26), positioned approximately three helical turns apart, as in the wild-type promoter. This synthetic promoter efficiently drove transcription of the U2 gene in transfected protoplasts of Nicotiana plumbaginifolia. The importance of the individual elements and of their position within the promoter was investigated. Deletion of the USE, change of its orientation, and some single point mutations all decreased transcription 10- to 20-fold, and replacement of the TATA-like element by an unrelated sequence inactivated the promoter. Mutants in which the spacing between the USE and TATAAATA was changed were less active but no correlation was observed between promoter activity and insertion of either odd or even numbers of half helical turns. Insertion of a spacer between TATAAATA and the cap site resulted in accumulation of U2 RNA with an extended 5' end, indicating that the TATAAATA element is responsible for selection of the initiation site. The data indicate that the promoters of RNA polymerase II-specific U-snRNA genes in higher plants differ from their animal counter-parts and also from plant mRNA gene promoters. They contain two essential elements, an USE, an element found only in U-snRNA genes, and a TATA element which is indistinguishable from the TATA boxes of mRNA-coding genes.